Future Health Today: codesign of an electronic chronic disease quality improvement tool for use in general practice using a service design approach. Issue 12 (18th December 2020) - Hunter, Barbara; Biezen, Ruby; Alexander, Karyn; Lumsden, Natalie; Hallinan, Christine; Wood, Anna; McMorrow, Rita; Jones, Julia; Nelson, Craig; Manski-Nankervis, Jo-Anne
Abstract : Objective: To codesign an electronic chronic disease quality improvement tool for use in general practice. Design: Service design employing codesign strategies. Setting: General practice. Participants: Seventeen staff (general practitioners, nurses and practice managers) from general practice in metropolitan Melbourne and regional Victoria and five patients from metropolitan Melbourne. Interventions: Codesign sessions with general practice staff, using a service design approach, were conducted to explore key design criteria and functionality of the audit and feedback and clinical decision support tools. Think aloud interviews were conducted in which participants articulated their thoughts of the resulting Future Health Today (FHT) prototype as they used it. One codesign session was held with patients. Using inductive and deductive coding, content and thematic analyses explored the development of a new technological platform and factors influencing implementation of the platform. Results: Participants identified that the prototype needed to work within their existing workflow to facilitate automated patient recall and track patients with or at-risk of specific conditions. It needed to be simple, provide visual snapshots of information and easy access to relevant guidelines and facilitate quality improvement activities. Successful implementation may be supported by: accuracy of the algorithms in FHT and data held in the practice; the platform supporting planned and spontaneous interactions with patients; the ability to hide tools; links to Medicare Benefits Schedule; and prefilled management plans. Participating patients supported the use of the platform in general practice. They suggested that use of the platform demonstrates a high level of patient care and could increase patient confidence in health practitioners. Conclusion: Study participants worked together to design a platform that is clear, simple, accurate and useful and that sits within any given general practice setting. The resulting FHT platform is currently being piloted in general practices and will continue to be refined based on user feedback.